2017
DOI: 10.1021/acsami.7b02794
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Electrochromic Properties of Nanocellulose-Based Polyaniline Nanocomposite Films

Abstract: On the basis of nanocellulose obtained by acidic swelling and ultrasonication, rodlike nanocellulose/polyaniline nanocomposites with a core-shell structure have been prepared via in situ polymerization. Compared to pure polyaniline, the nanocomposites show superior film-forming properties, and the prepared nanocomposite films demonstrate excellent electrochemical and electrochromic properties in electrolyte solution. Nanocomposite films, especially the one prepared with 40% polyaniline coated nanocomposite, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(75 citation statements)
references
References 52 publications
1
72
1
1
Order By: Relevance
“…In the case of organic matrix, a wellknown approach to generate inorganic nanophases within an organic matrix is to utilize sol-gel chemistry [18]. Inorganic sol-gel precursors such as silicon, titanium, aluminum, and zirconium metal alkoxides are employed in the formulation of nanocomposite coatings.…”
Section: Sol-gel Methodmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of organic matrix, a wellknown approach to generate inorganic nanophases within an organic matrix is to utilize sol-gel chemistry [18]. Inorganic sol-gel precursors such as silicon, titanium, aluminum, and zirconium metal alkoxides are employed in the formulation of nanocomposite coatings.…”
Section: Sol-gel Methodmentioning
confidence: 99%
“…For organic matrix, called polymer-based nanocomposite, the most used polymers for preparation of nanocomposite coating can be listed as follows: epoxy [2][3][4][5][6][7], polyurethane [8,9], Chitosan [10,11], polyethylene glycol (PEG) [12][13][14][15], polyvinylidene fluoride (PVDF) [16], PANi [17][18][19], PPy [20][21][22][23], polystyrene [24], polyamic acid and polyimide [25], rubber-modified polybenzoxazine (PBZ) [26], polymers containing reactive trimethoxysilyl (TMOS) [27], pullulan [28], fluoroacrylic polymer [29,30], ethylene tetrafluoroethylene (ETFE) [31], polyacrylate [3], poly(N-vinyl carbazole) [32], polycarbonate [33], fluorinated polysiloxane [34], polyester [35], polyacrylic [36], polyvinyl alcohol (PVA) [37], polydimethylsiloxane [38], polyamide [39], and UV-curable polymers [40].…”
Section: Materials For Matrixmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of corrosion protection by PANI is related to both barrier and electrochemical protection effects, whereby increases in corrosion potential and passivation layer formation lead to an effective corrosion rate reduction on metal surfaces. (10)(11)(12)(13)(14)(15)(16)(17) Recently, a considerable number of publications associated with polymer-clay or polymer-silica nanocomposites have been reported regarding effectively improved anticorrosive properties. It has been shown that montmorillonite clay and nanosilica can enhance the anticorrosive effect of polymer coatings, owing to the enhancement of barrier properties by increasing the lengths of diffusion pathways for oxygen and water.…”
Section: Introductionmentioning
confidence: 99%